A strategic sourcing evaluation methodology for reshoring decisions. Issue 3 (2nd July 2016) - Presley, Adrien; Meade, Laura; Sarkis, Joseph
ABSTRACT: Decisions regarding offshoring and reshoring of manufacturing facilities and processes are of strategic importance for companies. These decisions often require the consideration of multiple financial, quantitative and qualitative factors. Integrating these often disparate factors can be extremely difficult for managers. This article presents a methodology, based on expert and practitioner input and literature, which aids in this process. The methodology incorporates concepts from activity-based costing, multi-attribute decision making and utility theory. An illustrative example using factors derived from literature and practice is presented to demonstrate the methodology and to discuss the issues which must be considered when making offshoring/reshoring decisions. The results of a series of interviews with supply chain professionals to establish the validity of the approach are discussed.